Self-prefixed verbs: Analogy in the Functional Discourse Grammar lexicon. (March 2018) - Mackenzie, J. Lachlan
Abstract : This article takes an analogy-based approach to the analysis of morphological derivation in the framework of Functional Discourse Grammar (FDG), giving an account of English verbs with the prefix self -. Such self -prefixed verbs call on different lexical frames, namely one-place, two-place and two- and three-place reflexive frames. Their use stands in a complex relation with either reflexive or intensifying interpretations, or indeed both. In two-place frames, where the self -prefixed verb takes an object or other complement, that object/complement is bound by the subject. Various factors predisposing speakers to use self -prefixed verbs are considered, outlining how these relate to other self -prefixed lexemes in a network of analogical relations.